2007
DOI: 10.1002/micr.20416
|View full text |Cite
|
Sign up to set email alerts
|

Free SCIA/SIEA skin flap: A dual blood supply approach to groin region

Abstract: Free groin flap donor skin is unequaled in generous skin supply and inconspicuousness. We reliably utilize this region by taking advantage of the dual blood supply from superficial circumlex iliac (SCIA) and superficial inferior epigastric (SIEA) arteries and name the flap "Free SCIA/SIEA skin flap." The arterial pedicle is selected between SCIA and SIEA according to vascular anatomy which is explored through an incision along the inguinal ligament prior to skin island planning. Among 57 free SCIA/SIEA skin fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In our previous study, we demonstrated that these vessels are supplied by the same skin island and large flaps may be elevated safely as based on SCIA and/or SIEA pedicles. 1 This flap was our first preference in soft tissue reconstruction of the lower extremity (64%; 27 free SCIA/SIEA flap/42 total flaps: free SCIA/ SIEA, latissimus dorsi, rectus abdominis, superficial temporal). No area of the body has benefited more from free flap transfer than the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated that these vessels are supplied by the same skin island and large flaps may be elevated safely as based on SCIA and/or SIEA pedicles. 1 This flap was our first preference in soft tissue reconstruction of the lower extremity (64%; 27 free SCIA/SIEA flap/42 total flaps: free SCIA/ SIEA, latissimus dorsi, rectus abdominis, superficial temporal). No area of the body has benefited more from free flap transfer than the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…1 We selected SIEA, which was preferred, when the intended result was a thick flap while SCIA was used for reconstruction with a thin flap. The selected arterial pedicle was SCIA (n ϭ 9), SIEA (n ϭ 15), or their common trunk (n ϭ 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aydin and Nasir were able to close the donor sites of groin flaps primarily without any postoperative problems even in the largest flap size they harvested. (21) The groin flap is commonly employed in free tissue transfers for defects of the extremities. (22) The popularity of this flap, however, has gradually decreased in recent years (23) because of disadvantages related to its short pedicle, frequent structural variations and technically demanding harvesting.…”
Section: Groin Flapmentioning
confidence: 99%
“…We reported that the skin of the lower abdominal and groin regions may be elevated based on the SCIA and/or SIEA. 3 To facilitate flap thinning, we used a simple method for the free SCIA/SIEA flap. In this study, we present details of our thinning methods for free SCIA/SIEA flaps.…”
mentioning
confidence: 99%